ECO-INNOVATIVE STRATEGIES: ENHANCING ENVIRONMENTAL AWARENESS AND SHAPING CONSUMER PREFERENCES THROUGH GREEN MARKETING - Prasetyo Nurhidayat; Sonia Melati Indah; Ayu Vebiola; Sandri Atmanegara; Ana Nurhasanah; Ade Octavia (JOURNAL OF BUSINESS STUDIES AND MANGEMENT REVIEW, 2023)
This study delves into the burgeoning field of green marketing and its pivotal role in shaping environmental awareness and influencing consumer preferences. Positioned within the realm of marketing management, this research sets the groundwork for developing hypotheses about the dynamics between green marketing and various dependent variables, aiming to guide future empirical investigations. Employing a qualitative descriptive approach, this research synthesizes insights from an extensive review of academic literature, utilizing resources such as Crossref, Google Scholar, and other esteemed academic platforms. The findings underscore two primary impacts of green marketing: (1) a significant influence on consumer environmental consciousness, and (2) a notable effect on consumer preferences. Beyond these key areas, the study identifies additional factors interplaying with green marketing. These include competitive advantage, environmental sustainability, brand image, Eco Labelling, and Eco Branding. These insights contribute to a more nuanced understanding of green marketing's multifaceted influence and highlight potential avenues for further research in the field.